World agriculture : towards 2010 : an FAO study - Alexandratos, Nikos ed. (FAO RomeIT, 1995)
Assesses the prospects, worldwide, for food and agriculture, including fisheries and forestry, over the years to 2010. Focuses on food security, natural resources and sustainability.